Microbiological Quality of Raw Goat Milk in Bogor, Indonesia - E Taufik; G Hildebrandt; J N Kleer; T I Wirjantoro; K Kreausukon; K H Zessin; M P.O Baumann; F H Pasaribu (Faculty of Animal Science, Bogor Agricultural University, 2011)
Milk samples were investigated for counts and prevalence of indicator bacteria, which were TPC, coliforms, coagulase positive Staphylococci (CPS), and coagulase negative Staphylococci (CNS). Ten potential risk factors were also evaluated in relation to the prevalence of indicator bacteria. The results showed that the median values of indicator bacterial counts from overall udder-half milk samples were 3.74, 0.70, 1.70, and 2.52 log cfu/ml and from bulk milk samples were 5.69, 2.98, 3.66 and 3.32 log cfu/ml for TPC, coliforms, CPS, and CNS, respectively. None of the median values of overall udder-half milk samples exceeded the maximum limit of the standards for all indicator bacteria. However, in the bulk milk samples only the median value of TPC below the maximum limit of the standards. Overall prevalence of coliforms, CPS and CNS from udder-half milk samples were 46.3%, 37.7%, and 66.0%, respectively, and from bulk milk samples were 86.7%, 76.7%, and 86.7%, respectively. Saanen crossbreed, fifth parity and udders with inflammation were found to be risk factors. This study results indicated that the hygienic practices in the dairy goat farms are still need to be increased. To increase the hygienic level of the milk, the identified significant risk factors must be controlled.